Dry fermentation to produce biogas - Nuraini Atikah, Mohammad (2018)
The rising of population size in Malaysia has definitely causing the usage of energy also increasing. In numbers, according to the National Energy Balance, 2008, Malaysia has stated a rise in basic energy usage at rate of 6.1 % per year between 2000 until 2008. This value also is getting nearer to the average annual increase in GDP in 6% in the same period. Thus, green technology is introduced to help in reducing the energy usage. Green technology can exist in form of energy, which includes the development of alternative fuels and that means new efficient energy can be generated. Some of industrial sector in Malaysia also have transforming their energy source into this alternative energy. One of the new sources of alternative energy is the bioenergy. Bioenergy which comes from bioethanol, biodiesel, and biogas has seen to become a good alternative and in this project, biogas is the source of energy that going to be produce. Biogas is an energy sources that can be produced from either wet fermentation or dry fermentation through anaerobic digestion process. Dry fermentation has become the main highlight in this project as it used minimal water supply, smaller reactor , and does not use any stirrer during the ongoing process thus less energy is used. Few reactors needed to be built so that the fermentation process can take place in it. Through this dry fermentation, anaerobic digestion will occur where the organic material is broken by the microorganisms and resulting the biogas being released. Content of the biogas will be analyse and measure by using the water displacement method. The biogas later can be used as an alternative to heat and electricity generation and natural gas substitute. This paper will focus on different type of reactor design on the movement of microorganism to react with biomass and start anaerobic process to produce biogas. Arrangement of organic material in the reactor itself and the hydraulic retention time also will be studied further. This paper also will discuss on designs and fabrication of a dry fermenter and to study the fermenter performance.